Bacillus pumilus and Paenibacillus lautus effectivity in the process of biodegradation of diesel isolated from hydrocarbons contaminated agricultural soils - Amparo Mauricio-Gutiérrez; Rocío Machorro-Velázquez; Teresita Jiménez-Salgado; Candelario Vázquez-Crúz; María Patricia Sánchez-Alonso; Armando Tapia-Hernández (Archives of Environmental Protection, 2020)
In Mexico, one of the principal natural resources is oil, however, the activity related to it has generated hydrocarbon spills on agricultural soils. The aim of this study was to evaluate the biodegradability of diesel by means of indigenous bacteria isolated from agricultural soil contaminated with 68 900 mg kg -1 diesel. We examined indigenous bacterial strains in agricultural soils contaminated with diesel from Acatzingo, Puebla, Mexico. We performed a physicochemical soil characterization, and a bacterial population quantification favoring sporulated bacteria of the genera Bacillus and Paenibacillus taken from the study site. Six bacterial strains were isolated. The identification was made based on the 16S rRNA gene and API systems. The tolerance and biodegradation capacity in diesel were determined at 4 000 to 24 000 mg L -1 of diesel. Residual concentrations of diesel were determined by GC-FID. Soil contaminated with diesel alters the concentrations of organic matter, phosphorus and nitrogen. Analysis of soil samples showed heat resistant bacterial populations of 106 cfu g -1 dry soil. Six strains from soil pollution were identified – Pseudomonas stutzeri M1CH1, Bacillus pumilus M1CH1b, Bacillus cereus M1CH10, Bacillus subtilis M1CH15a, and Paenibacillus lautus strains M1CH19 and M1CH27. These bacteria showed different degradation behavior. Bacillus pumilus M1HC1b and Paenibacillus lautus M1CH27 use diesel oil as the sole carbon source. Bacillus pumilus degraded high concentrations of diesel (24 000 mg L -1), while for Paenibacillus lautus it became toxic and the degradation was less.